Fishes of the Western North Atlantic. class Osteichthyes, order Acipenseroidei, order Lepisostei, order Isospondyli, suborder Elopoidea, suborder Clupeoidea, suborder Salmonoidea /: class Osteichthyes, order Acipenseroidei, order Lepisostei, order Isospondyli, suborder Elopoidea, suborder Clupeoidea, suborder Salmonoidea. Soft-rayed bony fishes : Part 3, ([2018]) - Bigelow, Henry Bryant, 1879-1967; Bradbury, Margaret G (Margaret Gertrude); Dymond, J. R (John Richardson), 1887-1965; Greeley, John R; Hildebrand, Samuel F (Samuel Frederick), 1883-1949; Mead, Giles W (Giles Willis), 1928-2003; Miller, Robert R, 1929-; Rivas, Luis Rene; Schroeder, William C (William Charles), 1895-; Suttkus, Royal D; Vladykov, Vadim D (Vadim Dmitrij), 1898-1986
No abstract available